Closed-loop evaluation on potential of three oil crops in remediation of Cd-contaminated soil. (15th August 2022) - Wang, Kaiyue; Li, Youwei; Liang, Chanjuan
Abstract: Cd-contaminated farmlands threaten food security and safety by inhibiting crop growth and Cd accumulating in edible parts. Phytoremediation is a promising option to remove Cd from farmland soil. An ideal option is to remediate Cd and produce crops simultaneously on the contaminated soil. Therefore, we chose widely planted oil crops (soybean, sunflower and rape) as experimental materials, cultured in pots filled with soils contaminated with different concentrations (10, 20, 50, and 100 mg kg −1 ) Cd till harvest, and then took a closed-loop method to evaluate the remediation potential of the three oil crops, including the remediating ability, yield, and quality of seeds and environmental risk of pyrolytic biochar. The results show that the order of Cd accumulation capacity in the three oil crops was sunflower > rape > soybean. The yield and quality of the three oil crops were decreased by being treated with different concentrations of Cd. In addition, the order for a decreased degree in yield of the three oil crops was sunflower < rape < soybean, and the order for a decreased degree in protein and fat content was sunflower < soybean < rape. The potential risk of seeds of the three oil crops as food/feed was sunflower/soybean < soybean/sunflower < rape. After pyrolysis of harvested three oil crops, the order for leaching toxicity/leaching potential was sunflower-biochar < soybean-biochar/rape-biochar < rape-biochar/soybean-biochar. All three oil crops could remediate Cd-contaminated soils, and their seeds could generate economic value. Closed-loop evaluation of sunflower proved it might be a good option for removing Cd from farmland soil. Highlights: An ideal phytoremediation option is to remediate Cd and produce crop simultaneously. Closed-loop evaluation was feasible to screen ideal crops for Cd phytoremediation. Larger biomass of sunflower was probably the reason of higher remediating ability. Lower leaching potential of Cd in sunflower-biochar profited environmental acceptance. Close-loop evaluation of sunflower proved it was good option for removing Cd in soil.